PENGARUH JARAK NOZZLE DAN KOMPOSISI KOMPOSIT RAM PADA PELAPISAN BAM DAN PANI SEBAGAI MATERIAL ABSORBEN MENGGUNAKAN SPRAY GUN - Ayu Honey Djasindi; Roni Novison; Jupri Yanda Zaira (Politeknik Caltex Riau, 2021)
In the application of radar, it can be detected based on the radar cross section where RCS is used as a tool to reduce the value of the radar. RCS has four designs, one of which is Radar Absorbing Material. In this study, Barium M-Hexaferrite (BaM) was used as a magnetic material and a conductive polymer Polyaniline (PAni) as an electrical material. Barium M-Hexaferrite was used in this study with Cu doping which has a radius of 0.71 nm. Conductive Polymer Polyanilineis a material that is able to conduct electricity and can be used to protect electromagnetic waves generated from electricity. Both materials are coated with Jotun epoxy paint which will be applied to the black steel plate using the spary gun method. The research was shown at the nozzle distance (10, 15, 20 cm) and the composition of RAM(19.8, 1.76, 0.30 gr). The test used thicknesstest,hardness test, roughness test, and VNA test. From the data that has been obtained good absorption is known from the VNA test, namely at a nozzle distance of 20 cm with a reflection loss value of -5.6262db at an absorption frequency of 11.18 GHz andthe value of the composite composition of RAM is 0.30 gr with a reflection loss value of -5.6262 db.